Updates on the oversight role of the Algerian Accounting Board on the work of the Algerian Accounting Council - diaf, yassamina (Journal of Research in Finance and Accounting, 2022)
The Developments in the oversight role of the work of the Court of Accounts as a constitutional institution, based on the subsequent control of the disbursement and management of public funds by supporting the independence and transparency of the work of the Board in order to combat corruption and preserve public money, by devoting a set of guarantees represented in: Appointing the head of the Court of Accounts according to the system of contracts, which is This makes him independent in performing his work throughout his tenure, and enhances the transparency of the Council's work by publishing its work before public opinion, which allows for the exercise of popular oversight.